A rule against murder - Penny, Louise (Penny, Louise. Three Pines mystery, 2009)
In this classic drawing room mystery, Chief Inspector Armand Gamache is looking forward to celebrating his wedding anniversary at the remote, luxurious Manoir Bellechasse. As Gamache's holiday becomes a busman's anniversary, he learns that the seemingly peaceful lodge is a place where visitors come to escape their past, until that past catches up with them.